Tuberous sclerosis complex: review based on new diagnostic criteria - Larissa Karine Leite Portocarrero; Klícia Novais Quental; Luciana Paula Samorano; Zilda Najjar Prado de Oliveira; Maria Cecília da Matta Rivitti-Machado (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Tuberous sclerosis complex is a multisystemic, autosomal dominant genetic disorder with complete penetrance, that can evolve with hamartomas in multiple organs, such as skin, central nervous system, kidney and lung. Due to the wide phenotypic variability, the disease is often not recognized. Tuberous sclerosis complex affects one in 10,000 newborns and most patients are diagnosed during the first 15 months of life. The diagnostic criteria for tuberous sclerosis were reviewed in 2012, at the second International Tuberous Sclerosis Complex Consensus Conference. The diagnosis is based on genetic criteria, by the identification of inactivating pathogenic mutation of tumor suppressor genes TSC1 and TSC2, and clinical criteria, including cutaneous, renal, pulmonary, cardiac and neurological manifestations. The treatment of tuberous sclerosis complex consists, mainly, in management of the symptoms caused by hamartomas and in prevention of organ failure. Multidisciplinary approach is recommended, in order to obtain better clinical outcomes.